Availability and utilization status of indigenous ornamental fishes in Bilaspur fish market, Chhattisgarh - Rajesh Kumar; Vipul Singh Badguzar; Shashi Jatwar; Sheetal K Bharda; Honnananda R Badami; Zaheer Abass (Journal of Indian Fisheries Association, 2023)
A study on the availability and utilization status of indigenous ornamental fishes in the Bilaspur fish markets was carried out. Primary data on the availability of indigenous fish species in Bilaspur city was collected from two main local fish markets (Budhwari fish market and Sanichari fish market) and several ornamental fish shops. In this study, a total of 10 species of indigenous ornamental fish belonging to five different orders and seven families were identified. The most dominant order was the Cypriniformes (40%), followed by the Siluriformes (30%) and other orders. With four different fish species (Brachydanio ratio, Osteobrama cotio, Puntius ticto, and Salmostoma bacaila), the Cyprinidae family was the most prevalent, followed by Siluridae (Ompak bimaculatus), Bagridae (Mystus tengara), Pangasidae (Pangasius pangasius), Notopteridae (Notopterus notopterus), Channidae (Channa marulius), Ambassidae (Chanda nama). All the indigenous ornamental fishes present in the Sanichari fish market and Budhwari fish market were used as food fish, whereas the fishes present at ornamental fish shops were utilized for ornamental purposes.